STUDENTS'PERSPECTIVE ON YOUTUBE AS LEARNING MATERIAL FOR LISTENING OUTSIDE THE CLASSROOM - Muhammad Faishal Dzaky (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Dzaky, Muhammad Faishal. 2022. Students' Perspective on Youtube as Learning Material for Listening Outside the Classroom Skripsi, English Education Department Faculty of Teacher Training and Education University of Islam Malang. Advisor I : Dr. Kurniasih, S.Pd., M.Pd.. Advisor II :Nuse Aliyah Rahmati, S.Pd., M.A. TESOL Abstract: Listening is considered as fundamental language skills to receive and messages delivered through voice and sound in the communication process. In terms of communication, authentic material is essential in listening class in order to make the students familiar with how English are used in actual life. There are many ways to develop listening skills with the help of advances in technology. One of many methods where EFL learners can practice their listening skills is by watching English video. One of the most popular Video platform containing many authentic material is Youtube. Therefore the researcher interested in conducting the research about students’ perception on the implementation of YouTube in online class. This research is conducted using descriptive qualitative research to answer the research questions. The participants in this study consist of 10 students, from the 3rd semester in English language department at the University of Islam Malang. The instrument used in this study is in the form of semi-structured interview about the implementation of YouTube in online listening class. The data analysed using qualitative data analysis including, reduction, coding, grouping, interpretation and conclusion.The result shows that all the students enjoy the implementation of YouTube in online listening classes. YouTube is implemented mostly for learning material, its implementation provide visual support, repeatability and flexibility. The study also showed that the students can learn independently by the availability of references and information that are updated regularly. Moreover, materials on YouTube are provided authentically by English natives. The result also indicated that the disadvantage of YouTube is when the students rely too much on repeatable features. This study also indicated that the role of the lecturer to guide the students to the right material is still essential in learning.Keywords: Perception, YouTube, Learning Media.